Gestión de proveedores y su influencia en el servicio al cliente en la Ferretería Orzac & Cris S.A.C. Huamachuco año 2017 - Calderon Avila, Zaira Leonor (2017)
The present thesis was carried out in the city of Huamachuco, province of Sánchez Carrion, Department of La Libertad, Peru. Its main objective is to determine how Supplier Management influences Customer Service at the Orzac & Cris SAC hardware store in the city of Huamachuco, in 2017. The research problem was: How does Supplier Management Influente In Customer Service at Orzac & Cris SAC Hardware; Huamachuco, year 2017? In the collection of data, three populations were taken into account, the first one comprising 22 main customers, the second by 10 suppliers and the third by the administrator of the hardware store under study, the sample being the same as the populations; the techniques of data collection were the survey, documentary analysis and interview. According to the results obtained, the corresponding discussion has been carried out, demonstrating the validity of the hypothesis: "Supplier Management has a positive and significant influence on Customer Service at Orzac & Cris S.A.C; Huamachuco, year 2017". The respective conclusions and recommendations were also made; Concluding that both study variables qualify as "High" with a "Medium" tendency, and statistically it has been shown that Supplier Management strongly influences Customer Service (Pearson Correlation Coefficient r = 0.989). Said "significant" correlation in accordance with the results of the SPSS program. In view of this, it is recommended to implement improvements in "suppliers management", both in the research stage, searching for new suppliers of materials, visiting them to request samples, quotes and more favorable payment conditions; And in the Evaluation stage, the selection criteria should be made more flexible, taking into account the organizational, economic and financial reality of the hardware, as well as the requirements of its customers.